If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 747 + (-60x) = 0 Solving 747 + (-60x) = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-747' to each side of the equation. 747 + -747 + (-60x) = 0 + -747 Combine like terms: 747 + -747 = 0 0 + (-60x) = 0 + -747 (-60x) = 0 + -747 Combine like terms: 0 + -747 = -747 (-60x) = -747 Divide each side by '-60'. x = 12.45 Simplifying x = 12.45
| 6(x-8)+54=60 | | 42=49-v | | 2.02b+4.30=2.00b+6.30 | | 2(x)+4(y)=20 | | 5/9w=-1/4 | | 2(x)+4(y)=64 | | 6/24=t/108 | | 9(x+5)+8x=164 | | 747+(-60)=300 | | x(x+12)=(x-4)2 | | X+750=3200 | | x=26-57 | | 5(3x+2)=-3(2x-4)-4x | | 174=121-w | | 31=-4x-5x-5 | | 2e^4x+7=107 | | 182=42-y | | 9u+4u=30 | | 747+(-60)=0 | | 1/8x−49/8 | | 188=29-x | | 6(3x-3)(x-4)=0 | | 43-y=174 | | 6g+27=36 | | y+63=8y | | (x-7)(-1)=0 | | .08=.03+.60*.05 | | 10y=21+7y | | .08=.03+.03 | | 3x+5=2(2x-1)1-(x-3) | | -3/5c-7=6 | | 227=142-u |